Correlation Between Serum Il-24 Level in Acne Vulgaris Patients of Varying Clinical Severity - Annisa Marsha Evanti; Muhammad Eko Irawanto; Nurrachmat Mulianto; Arie Kusumawardani; Endra Yustin Ellistasari (Journal of Social Research, 2026)
Background: Acne vulgaris (AV) is a chronic inflammatory disorder of the pilosebaceous unit that significantly impacts patients' quality of life. The inflammatory process involves immune responses partially regulated by IL-24, suggesting its potential role in AV pathophysiology and clinical severity. However, data on serum IL-24 levels based on AV severity remain limited, particularly in Indonesia. This study aims to evaluate the relationship between serum IL-24 levels and acne vulgaris severity to further elucidate its molecular mechanisms. Methods: This observational analytical study with a cross-sectional design was conducted at Dr. Moewardi General Hospital, Surakarta, Indonesia, from November 2025 to January 2026, involving healthy individuals and acne vulgaris patients. AV severity was assessed using the Lehmann classification, and serum IL-24 levels were measured by ELISA. Results: A total of 60 subjects were involved, consisting of 15 healthy controls, 15 patients with mild AV, 15 with moderate AV, and 15 with severe AV. Pearson correlation analysis showed no significant relationship between serum IL-24 levels and AV severity (p = 0.186). However, there was a trend towards increasing serum IL-24 levels along with acne severity. In the healthy control group, IL-24 levels were lower than in the AV group. Conclusions: Serum IL-24 levels are not associated with acne vulgaris severity. This is likely due to its effect on local keratinocyte proliferation. Further research is needed to elucidate the pathophysiology using histopathological examination of skin tissue from patients with AV